Alterations in expression of miRNA 497 and long non-coding RNAS (XIST–TSIX) and its significant role in colorectal cancer prediction - El-Magied, Mohamed Hassan Abd; Fawzy, Amal; Mostafa, Marwa Mohsen; Elnaggar, Ghada Nabil; Moselhy, Said Salama; Elhady, Mostafa Mohamed (Scientific reports, 2025)
Colorectal cancer (CRC) is a common type of malignancy in Western nations with high incidence related to different factors as genetic, foods and pollution. Long non-coding RNAs (LncRNAs) play a significant role in cellular processes, oncogensis and can be used as biomarkers for cancer progression. The rationale of this study was to quantify the expression levels of miRNA 497 and LncRNAs (XIST–TSIX) as a sensitive and accurate markers for CRC diagnosis and correlated with serum FOXK1, CA19.9 and CEA compared with normal subjects. This study was carried outon100 participants, they were divided into two equal groups: Group (1): Patients were diagnosed with CRC and Group (2): Normal subjects as control. Tumor size, type, TNM staging, differentiation, levels of FOXK1and, CEA, CA19.9 were evaluated in serum. The RNA was extracted from the tissue of CRC patients for quantification expression of miRNA 497 and LncRNAs (XIST and TSIX) using qRT-PCR. Data obtained showed that, the expression levels of tissue miRNA 497, XIST, TSIX in combination with serum FOXK1, CA19.9 and CEA are good confirmatory non-invasive markers for CRC diagnosis. Sensitivity and specificity tests showed higher AUC values of miRNA 497 + XIST + TSIX + FOXK1 significantly than those of CA19.9 + CAE. It was concluded that, a rigorous assessment of these parameters could facilitate the discovery of non-invasive biomarkers for the early detection and prognosis of CRC, ultimately enhancing the protocols for early treatment decision-making.